Carbohydrate ingestion and the immune system during prolonged exercise - Pyne, D. B.; Burke, L. M. (International SportMed Journal, 2000)
Immunosuppression is associated with the prolonged strenuous training schedules undertaken by many athletes, placing them at an increased risk of illness and infection. Nutrition is also known to affect immune status, and recent studies have identified that CHO intake may play an important role in maintaining effective immune function in athletes. Two principal mechanisms linking low carbohydrate intake and disturbed immune function have been investigated: direct immunosuppression due to the depletion of glucose, a key substrate for immune cells, and indirectly via increased concentration of stress hormones. Current sports nutrition guidelines endorse various strategies for promoting CHO availability to the central nervous system and exercising muscle(s). These include guidelines to consume CHO before, during, and after prolonged exercise sessions. Although the primary benefit is likely to be the availability of fuel supply, leading to better training or competition performance, protection of the immune system may be a secondary but substantial benefit of these strategies. Further studies are needed to link favorable changes to various immune parameters following CHO intake strategies with reduced frequency or severity of illness in athletes.